simplify the rational expression
((1/x+1)+(1/x+2))/((1/x+2)+(1/x+3))= ()/()
((1/x+1)+(1/x+2))/((1/x+2)+(1/x+3))= ()/()
(1/(x+1))+(1/(x+2))/(1/(x+2))+(1/(x+3))=
Simply the following rational equation (x-5/x2-25) - (3/x+5)= A/B where A and B are polynomials of degree as low as possible and the leading coefficient of B is 1. A= B= &...
I tried to multiply the 3-i on the top and bottom but then I get lost on what belongs on the bottom and on the top. I thought I would have something like 6-2i/9 but that doesn't...
This is for my trig class, thanks for the help!
This is for my trig class. Thanks for the help!
This is for my trig class. Thanks for the help!
This is for my trig class. Thanks for the help!
This is for my trig class. Thanks for the help!
The problem says: Simplify (3/2)^-2 I can't get the correct answer.
The directions say to simplify and write in standard form a+bi.
7 ln x - 1/4 ln y I would be very grateful for some help! Thanks for reading!
f(x) = 3x2 - 2x -3 f(x-1) = I would really appreciate the steps and final outcome of this problem. Thank you!
Find the distance. P1=(3,-3);P2=(1,4)
Use the Laws of Logarithms to combine the expression. 4 log x − (1/3)log(x2 + 1) + 5 log(x − 1)
f(X)=5-3x f(t)+(-2)=eval and simplefy
Simplify by factoring. Assume that all variables under radicals represent nonnegative, (Show all work) √81x^6
Simplify. Use positive exponents for any variables. (Show all work.) 2a^-4b^5/8a^2b^-3
Preform the indicated operation (Show All Work and Simplify the answer do not factor) (12x^3-2x^2-6x-3)-(-4x^3+10x^2-10x+1)
Use the Quotient rule to simplify. (Show all work) -20a^7b^c^9/5a^4b^2c^5